A time-driven activity-based costing approach of magnetic resonance-guided high-intensity focused ultrasound for cancer-induced bone pain. (31st December 2022) - Simões Corrêa Galendi, Julia; Yeo, Sin Yuin; Simic, Dusan; Grüll, Holger; Stock, Stephanie; Müller, Dirk
Abstract: Objective: To determine resource consumption and total costs for providing magnetic resonance-guided high-intensity focused ultrasound (MR-HIFU) treatment to a patient with cancer-induced bone pain (CIBP). Methods: We conducted a time-driven activity-based costing (TD-ABC) of MR-HIFU treatments for CIBP from a hospital perspective. A European care-pathway (including a macro-, meso-, and micro-level) was designed to incorporate the care–delivery value chain. Time estimates were obtained from medical records and from prospective direct observations. To calculate the capacity cost rate, data from the controlling department of a German university hospital were allocated to the modules of the care pathway. Best- and worst-case scenarios were calculated by applying lower and upper bounds of time measurements. Results: The macro-level care pathway consisted of eight modules (i.e., outpatient consultations, pretreatment imaging, preparation, optimization, sonication, post-treatment, recovery, and anesthesia). The total cost of an MR-HIFU treatment amounted to €5147 per patient. Best- and worst-case scenarios yielded a total cost of €4092 and to €5876. According to cost categories, costs due to equipment accounted for 41% of total costs, followed by costs with personnel (32%), overhead (16%) and materials (11%). Conclusion: MR-HIFU is an emerging noninvasive treatment for alleviating CIBP, with increasing evidence on treatment efficacy. This costing study can support MR-HIFU reimbursement negotiations and facilitate the adoption of MR-HIFU as first-line treatment for CIBP. The present TD-ABC model creates the opportunity of benchmarking the provision of MR-HIFU to bone tumor. Key points: Magnetic resonance-guided high-intensity focused ultrasound (MR-HIFU) is an emerging noninvasive treatment modality for alleviating cancer-induced bone pain (CIBP). From a hospital perspective, the total cost of MR-HIFU amounted to €5147 per treatment. This time-driven activity-based costing model creates the opportunity of benchmarking the provision of MR-HIFU to bone tumor.